2006
DOI: 10.1002/rcm.2464
|View full text |Cite
|
Sign up to set email alerts
|

Derivatization by 6‐aminoquinolyl‐N‐hydroxysuccinimidyl carbamate for enhancing the ionization yield of small peptides and glycopeptides in matrix‐assisted laser desorption/ionization and electrospray ionization mass spectrometry

Abstract: The characterization of glycosylation in proteins by mass spectrometry (MS) is often impeded by strong suppression of ionization of glycopeptides in the presence of non-glycosylated peptides. Glycopeptides with a large carbohydrate part and a short peptide backbone are particularly affected by this problem. To meet the goal of generating mass spectra exhibiting glycopeptide coverages as complete as possible, derivatization of glycopeptides offers a practical way to increase their ionization yield. This paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 54 publications
2
39
0
Order By: Relevance
“…Glycopeptides from human antithrombin, chicken ovalbumin, and bovine a1-acid glycoprotein could be detected in low fmol amounts (Ullmer, Plematl, & Rizzi, 2006).…”
Section: Derivatives Of Other Sitesmentioning
confidence: 99%
“…Glycopeptides from human antithrombin, chicken ovalbumin, and bovine a1-acid glycoprotein could be detected in low fmol amounts (Ullmer, Plematl, & Rizzi, 2006).…”
Section: Derivatives Of Other Sitesmentioning
confidence: 99%
“…When a suitable fluorescence labeling method can be linked with LIF detection, sensitivity can be strongly increased by up to 10 215 -10 218 mol for oligosaccharide samples [88]. For intact protein analysis, modified methods using preparative capillary ITP and CZE-ESI-TOF MS have been developed [89][90][91][92], and several kinds of glycoprotein, including ribonuclease B, recombinant human erythropoietin, and ovalbumin have been analyzed [87,93,94]. Intact human erythropoietin glycoforms were analyzed with CZE followed by ESI-TOF MS using capillary coating.…”
Section: Ce In Proteomicsmentioning
confidence: 99%
“…The detection sensitivity of some peptides could be increased over 40-fold via MALDI-TOF MS. Further research indicated that (7): [1123][1124][1125][1126][1127][1128][1129] coumarin derivatization was most pronounced for hydrophilic peptide signal enhancement [5] . Rizzi et al [23] used 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate (AQC) to derivatize peptides and evidently enhanced the signal intensity of glycopeptides and small peptides. By the further analysis of enzymatic digestion of a three glycoprotein mixtures (human antithrombin, chicken ovalbumin, and bovine a1-acid-glycoprotein), the limit of detection could be reduced to low fmol amounts.…”
Section: Derivatization Of Amino Groupmentioning
confidence: 99%